Kelincahan Remaja SMA Hang Tuah 4 Surabaya - Anastasia Putu Martha Anggarani (Jurnal Keterapian Fisik, 2019)
Background: The result of today's technological developments has stopped many people from natural exercise. Some of the jobs that exist, do not require us to move the body normally. If the jobs that exist do not make us move it will affect agility that will affect performance in carrying out activities. An description of agility is needed to identify the risk of decreased performance when doing activities in adolescents. Agility identification using an agility t test. Agility t test is a measuring instrument that has a reliability value of 0.98, good for measuring agility. The aim of the study was to identify the agility of the Hang Tuah 4 high school students in Surabaya. Method: The type of this research is descriptive, which is to describe the agility of the Hang Tuah 4 Surabaya high school students. Result: The average value of respondents' agility score is 19.66. All respondents have the category of poor agility. This is because most of the respondents in this study did not carry out routine exercise activities (53.1%). Sports activity is one of the factors that influence the improvement of agility. By carrying out routine sports activities, agility will be formed. Agility is a component that consists of aerobic endurance and muscle fitness, namely strength, muscle endurance and flexibility, reaction speed and motion, balance, power, and coordination. Interrelated components form an agility which is an important part of one's performance. Conclusion: To achieve this, the appropriate sports parameters are needed. One example is using the FIT principle, which includes: (1) Frequency of exercise 3 - 5 times a week, (2) Exercise intensity 60 - 90% of DNM, (3) Tempo / training duration 20 - 60 minutes in one practice time